Introduction to Molecular Biology - Peter Paolella (McGraw Hill Education, 2010)
This book places molecular genetics within the general framework of metabolism. In this way, the processes and mechanisms of gene function and control are seen as phenomena connected to other cell activities. Theoretical considerations and experimental data are kept to a minimum.